Molecular Docking Analysis of Phytocompounds from Ficus hispida Aagainst Epidermal Growth Factor Receptor Kinase Domain - Lavanya Burra (International Journal of Cell Biology and Cellular Functions, 2025)
The Epidermal Growth Factor Receptor (EGFR) kinase domain plays a key role in cancer, as it promotes tumour growth and helps cancer cells survive, making it an important focus for developing treatments. Through comprehensive computational analysis, this study investigates the anticancer potential of phytocompounds from Ficus hispida, a medicinal plant renowned for its diverse bioactive compounds, as novel EGFR inhibitors. Molecular docking techniques using Py Rx software were employed to evaluate the binding interactions of 34 Ficus hispida phytocompounds against the EGFR Kinase domain (PDB ID: 2ITN). Swiss ADME analysis assessed. The top-performing compounds for drug-likeness and pharmacokinetic properties. Protein structure validation was conducted using Ramachandran plot analysis, and molecular interactions were visualized using BIOVIA Discovery Studio. Four phytocompounds demonstrated exceptional binding affinities: Isoderrone (–9.2 Kcal/mol), Ficuisoflavone (–9.1 Kcal/mol), Ficusin A (–8.9 Kcal/mol), and Hispidacine (–8.9 Kcal/mol). All compounds satisfied Lipinski’s rule of five, exhibited favorable ADMET properties, and formed stable hydrogen bonds and hydrophobic interactions with key catalytic residues. The EGFR protein structure showed 85.1% residues in favourable regions, confirming structural reliability. Ficus hispida phytocompounds, particularly Ficusin A and Isoderrone, demonstrate significant potential as natural EGFR inhibitors with favourable pharmacokinetic profiles, warranting further experimental validation for anticancer drug development.
Keywords: ADME analysis; Cancer; EGFR kinase domain; Ficus hispida; drug discovery; molecular docking; molecular dynamics; phytocompounds